2017
DOI: 10.1016/j.jhtm.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A green step forward: Eliciting consumers' purchasing decisions regarding green hotel accommodation in Australia

Abstract: This study identifies beliefs and additional constructs that contribute to the formation of Australian residents' purchasing decisions of green hotel accommodation through the lens of the Theory of Planned Behavior (TPB). A qualitative approach using focus groups and open-ended questionnaires were employed to gain an in-depth understanding of the beliefs of travelers in the South East region of Queensland, Australia. The study utilizes thematic content analysis from three focus group discussions with 15 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 50 publications
2
35
0
2
Order By: Relevance
“…The studies indicated that environmental values influenced consumers' willingness to sacrifice for the biosphere, which then affected their green hotel visit intentions, their willingness to compromise to stay at a green hotel, and their willingness to pay more for such an accommodation. Nimri et al (2017) reported on similar findings. The results of their qualitative studies aimed at understanding the beliefs of travellers in the South East region of Australia, carried out on focus groups using open-ended questionnaires, led to the conclusion that "environmental beliefs" of customers are more important than their personal benefits.…”
Section: Financial Aspects Of Choosing Accommodation In Green Hotelssupporting
confidence: 63%
See 1 more Smart Citation
“…The studies indicated that environmental values influenced consumers' willingness to sacrifice for the biosphere, which then affected their green hotel visit intentions, their willingness to compromise to stay at a green hotel, and their willingness to pay more for such an accommodation. Nimri et al (2017) reported on similar findings. The results of their qualitative studies aimed at understanding the beliefs of travellers in the South East region of Australia, carried out on focus groups using open-ended questionnaires, led to the conclusion that "environmental beliefs" of customers are more important than their personal benefits.…”
Section: Financial Aspects Of Choosing Accommodation In Green Hotelssupporting
confidence: 63%
“…Ajzen, 1991;Ajzen and Fishbein, 2000;. It was recently suggested (Nimri, 2017) that although the theoretical foundation of the TPB theory could be used to analyse the consumers' purchasing decisions related to the green hotel accommodation in Australia, the model needs extension to account for the "Green Hotel Knowledge".…”
Section: Financial Aspects Of Choosing Accommodation In Green Hotelsmentioning
confidence: 99%
“…This partial interest may be associated with the conflicting results in prior studies regarding consumers’ decision-making behavior in terms of staying in green hotels. For instance, according to some studies, travelers favor booking at a hotel that incorporates pro-environmental practices due to their perception that by staying in such hotels, they might contribute to protecting the environment (Nimri, Patiar, & Kensbock, 2017; Rahman & Reynolds, 2016). Despite such a view, though, travelers were reluctant to stay in green hotels as they were concerned about compromising their luxury and comfort (Nimri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, according to some studies, travelers favor booking at a hotel that incorporates pro-environmental practices due to their perception that by staying in such hotels, they might contribute to protecting the environment (Nimri, Patiar, & Kensbock, 2017; Rahman & Reynolds, 2016). Despite such a view, though, travelers were reluctant to stay in green hotels as they were concerned about compromising their luxury and comfort (Nimri et al, 2017). Furthermore, some travelers were hesitant to stay in green hotels due to suspicions regarding the real motive of hotels’ green policies—perhaps a marketing ploy—thus eventually affecting the efficacy of hotels’ environmental programs (Rahman & Reynolds, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, more scholars have high intention to focus on the theory of planned behavior (TPB) and psychographic attributes to identify the decision of costumer to visit hotel (Chen et al, 2016;Kiatkawsin & Han, 2017;Nimri et al, 2017;Verma & Chandra, 2018). Some others have found that environmentally conscious consumer is more likely to seek high quality of environmentally product instead of price (Souza, 2007;Baker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%